First-principles study of two-dimensional bilayer GaN: structure, electronic properties and temperature effect. (23rd May 2019) - Yayama, Tomoe; Lu, Anh Khoa Augustin; Morishita, Tetsuya; Nakanishi, Takeshi
Abstract: The structural and electronic properties of bilayer GaN are investigated using first-principles calculations, focusing on the mechanism for stabilizing the flat and buckled bilayer structures of GaN. We confirm that, although the energy difference is small, the energy of the buckled models is lower than that of the threefold-coordinated flat model that had been regarded as the most stable bilayer GaN. In the buckled model, in contrast, a fourfold-coordinated atomic configuration is formed, which partially recovers the bulk crystalline structure and is likely to be one of the factors reducing the energy of bilayer GaN. While the flat model is not the most stable structure, there is a barrier to be overcome to transform, indicating that the flat model is a metastable structure. It appears that the existence of these multiple metastable structures is one of the unique characteristics of bilayer GaN.